The 6E approach to a healthy life - Sanjay Kalra; Madhur Verma; Nitin Kapoor (Journal of the Pakistan Medical Association, 2024)
us to focus on promotion of health and prevention of disease. Simple public health messaging is required to inform and motivate the public to follow evidence-based interventions which can help prevent metabolic illnesses and their complications. We present a catchy 6E framework which enjoins individuals to Eat well, Exercise well, Eliminate unhealthy behaviours/habits, Ensure adequate Entertainment, relaxation and sleep, practice Emotional control, and Eschew/avoid extremes. This message can be used at individual, family as well as public health levels, to spread awareness about healthy behaviours and lifestyle. Keywords: Diabetes, metabolic syndrome, obesity, prediabetes, prevention, primary care, primary prevention